VideoHound's golden movie retriever [2008] - Gale Group (Detroit, Mich. Gale, 2007)
Reviews movies that are available on DVD or tape. Each entry includes title, alternate title, one-to four-bone rating, year released, MPAA rating, brief review, length, format, country of origin, cast, technical personnel, awards and made-for-television/cable/video designations.
Electronic reproduction.
Keywords: Video recordings -- Catalogs -- Periodicals; Motion pictures -- Catalogs -- Periodicals; Motion pictures -- Plots, themes, etc. -- Periodicals; Electronic books